Mathematics teacher competency analysis during online learning - Jitu Halomoan Lumbantoruan; Bernadetha Nadeak (SAINTIS Publishing, 2022)
This study aims to find out where the difficulty of teacher competence is when implementing online mathematics materials. When online learning mathematics material, many students complain and get low learning outcomes. There are 92% of students have difficulty learning mathematics online. The basis of this problem needs to be analyzed where the difficulty of mathematics teacher competence in online learning. Data collection techniques with observations and shared instruments. The analysis is done by presenting the data, reducing it, and drawing conclusions. Results, 1) Online learning with the 2013 curriculum is still 95%. 2) There is no preparation and only the provision of package books. Student assessment of professional teacher competence 62% disagree and 45% pedagogically disagree, this disagreement is because the module was not prepared by the teacher himself. 3) 57, 14% disagree with the assessment method, the material being tested is more difficult than what is taught, and this is the cause of low learning outcomes. 4) Difficulty operating media, writing symbols, proving, explaining concepts, internet network, and correcting assignments. In conclusion, the difficulty lies in teachers with pedagogical competence with minimal learning aids and professional competence who cannot explain concepts in the media and are not assisted by self-made modules.